Solid-state electrolyte material and preparation method thereof, solid-state electrolyte sheet, and all-solid-state battery

CN117525562BActive Publication Date: 2026-10-16SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311769130.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2026-10-16
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本申请实施例的目的包括提供一种固态电解质材料及其制备方法、固态电解质片和全固态电池,以改善现有的固态电解质离子电导率较低的技术问题

Benefits of technology

[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117525562B_ABST
    Figure CN117525562B_ABST
Patent Text Reader

Abstract

The application relates to a solid-state electrolyte material and a preparation method thereof, a solid-state electrolyte sheet and a full-solid-state battery, and belongs to the technical field of full-solid-state batteries. y OHA my‑1‑nx B x ; wherein M is a metal cation with a chemical valence of m, A comprises one or more of F, Cl, Br and I, and B is a N-containing anion with a chemical valence of -n, n=1-3; M comprises one or more of Li + , Na + , K + , Mg 2+ , Ca 2+ , Sr 2+ , Zn 2+ , Y 3+ , La 3+ , Al 3+ , Ga 3+ , Ti 4+ and Zr 4+ . The electrolyte material is doped with N elements, which can increase ion vacancies in the crystal lattice, reduce the activation energy of ion transmission, and make ions more easily migrate in the crystal lattice, so that the ionic conductivity of the solid-state electrolyte material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of all-solid-state battery technology, and particularly to a solid electrolyte material and its preparation method, a solid electrolyte sheet and an all-solid-state battery. Background Technology

[0002] In recent years, rechargeable lithium-ion batteries have been widely used in portable electronic products, electric vehicles, and energy storage power stations due to their high energy density and long cycle performance. However, with the development of new energy vehicles and large-scale energy storage, increasingly higher requirements have been placed on lithium-ion batteries in terms of energy density, operating temperature range, cycle life, and safety performance. Replacing the volatile, flammable, and explosive organic electrolytes and gel electrolytes used in existing commercial lithium batteries with solid electrolytes can significantly improve their safety. Solid electrolytes possess characteristics such as high ionic conductivity, low electronic conductivity, wide electrochemical window, high energy density, good chemical stability, excellent interfacial compatibility, high mechanical strength, low cost, and safety and environmental friendliness. In addition, solid electrolytes also have advantages such as a wider electrochemical stability window for lithium metal anodes and the ability to effectively suppress lithium dendrite growth.

[0003] Among them, anti-perovskite solid electrolytes have advantages such as low activation barrier, low electronic conductivity, wide electrochemical window, good chemical stability to lithium metal, light weight, and environmental friendliness, showing promising application prospects. However, existing anti-perovskite solid electrolytes generally suffer from low ionic conductivity, which cannot well meet the requirements of secondary batteries and greatly limits their application. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the objectives of this application include providing a solid electrolyte material and its preparation method, a solid electrolyte sheet, and an all-solid-state battery, in order to improve the technical problem of low ionic conductivity in existing solid electrolytes.

[0005] In a first aspect, embodiments of this application provide a solid electrolyte material, including a cubic phase M y OHA my-1-nx B x Wherein, M is a metal cation with a chemical valence state of m, A includes one or more of F, Cl, Br, and I, and B is an N-containing anion with a chemical valence state of -n, where n = 1-3; M includes Li + Na + K + Mg 2+ Ca 2+ 、Sr 2+ Zn 2+ Y 3+ La 3+ Al3+ Ga 3+ Ti 4+ and Zr 4+ One or more of them.

[0006] The solid electrolyte material provided in this application is doped with nitrogen (N), which helps increase ion transport vacancies, i.e., introduces defects into the crystal lattice structure, thereby improving ion mobility. By optimizing the crystal structure through the introduction of N, the activation energy for ion transfer in the material is reduced, making it easier for ions to migrate within the crystal lattice, thus improving the ionic conductivity of the solid electrolyte material. Furthermore, this solid electrolyte material can form a cubic phase crystal with a stable structure. The stable structure helps improve the mechanical strength and chemical stability of the material, enabling it to maintain long-term cycling stability during use. The cubic structure gives the solid electrolyte an isotropic ion transport mechanism, further enhancing the ionic conductivity of the solid electrolyte material.

[0007] In some embodiments of this application, B includes N. 3- NH2 - and NH 2- One or more of the following. N 3- NH2 - and NH 2- The presence of nitrogen-containing anions in the crystal structure introduces additional bonds, enhancing lattice stability. This helps electrolyte materials maintain their structural integrity under different conditions (e.g., high temperature, high pressure), improving their long-term stability. Furthermore, the introduction of these nitrogen-containing anions can influence the lattice structure, altering charge balance and ion transport pathways, thereby modulating ion transport properties. For example, it can lower the activation energy for ion transfer in the lattice; by reducing this energy barrier, ions migrate more easily within the lattice, improving the ionic conductivity of the electrolyte material. In addition, these nitrogen-containing anions may also further enhance ionic conductivity by providing additional conductive pathways and optimizing ion migration within the lattice.

[0008] In some embodiments of this application, M is Li, and the solid electrolyte material includes an anti-perovskite cubic phase Li2OHA doped with Li2O. 1-nx B x Because this solid electrolyte material is doped with Li₂O, the Li₂O reacts with the anti-perovskite cubic phase Li₂OHA. 1-nx B x This forms a composite electrolyte, thereby further increasing the cycling stability of the electrolyte material.

[0009] In some embodiments of this application, cubic phase Li2OHA 1-nx B xIncluding anti-perovskite cubic phase Li2OHCl doped with Li2O 1-3x N x cubic phase Li2OHCl 1-x (NH2) x and cubic phase Li2OHCl 1-2x (NH) x At least one of them.

[0010] In some embodiments of this application, cubic phase Li2OHA 1-nx B x Including anti-perovskite cubic phase Li2OHCl doped with Li2O 0.85 N 0.05 cubic phase Li2OHCl 0.7 N 0.1 cubic phase Li2OHCl 0.4 N 0.2 cubic phase Li2OHCl 0.7 (NH2) 0.3 cubic phase Li2OHCl 0.6 (NH2) 0.4 cubic phase Li2OHCl 0.8 (NH) 0.1 and cubic phase Li2OHCl 0.6 (NH) 0.2 At least one of them.

[0011] Secondly, embodiments of this application provide a method for preparing a solid electrolyte material as described above, comprising: mixing raw materials according to a metered ratio and then ball milling them to obtain powder; pressing the powder into a blank to obtain a preform; and subjecting the preform to synthesis at 1-5 GPa and 300-800℃ for 30-60 min to obtain solid electrolyte material M. y OHA my-1-nx B x .

[0012] In this preparation method, ball milling can improve the uniformity and mixing degree of raw materials, promoting better mixing of various raw materials to form a homogeneous reactant mixture; it also helps to improve preparation efficiency and shorten reaction time; furthermore, by adjusting the synthesis conditions, such as high pressure (1-5 GPa), temperature (300-800℃) and synthesis time (30-60 min), it is beneficial to form a cubic phase crystal with a stable structure, which helps to improve the mechanical strength and long-term stability of the electrolyte material, while optimizing the ion transport path, thereby improving the conductivity.

[0013] In some embodiments of this application, the solid electrolyte material includes an anti-perovskite cubic phase Li2OHCl doped with Li2O. 1-3x Nx The raw materials include LiOH, LiCl, and Li3N, with a molar ratio of LiOH, LiCl, and Li3N of 1:(1-3x):x, and x = 0.05-0.2; or, the solid electrolyte material includes Li2OHCl, an anti-perovskite cubic phase doped with Li2O. 1-x (NH2) x The raw materials include LiOH, LiCl, and LiNH2, with a molar ratio of LiOH, LiCl, and LiNH2 of 1:(1-x):x, and x = 0.3-0.4; or, the solid electrolyte material includes Li2OHCl, an anti-perovskite cubic phase doped with Li2O. 1-2x (NH) x The raw materials include LiOH, LiCl and Li2NH, and the molar ratio of LiOH, LiCl and Li2NH is 1:(1-2x):x, and x = 0.1-0.2.

[0014] In some embodiments of this application, the ball milling process includes a total mass ratio of raw materials to milling beads of 1:(10-30). By limiting the total mass ratio of raw materials to milling beads to the range of 1:(10-30), the raw materials can be mixed evenly and ground thoroughly, achieving high efficiency and controllability in the ball milling process, thereby providing favorable reaction conditions for subsequent steps and improving the quality and performance of the final product.

[0015] In some embodiments of this application, the ball milling speed is 350-500 r / min, and the milling time is 6-12 h. Within this range of ball milling speed and time, sufficient mechanical energy input can be provided to promote thorough mixing and grinding between the raw materials and the milling beads. This helps eliminate particle inhomogeneity in the raw materials, forming a homogeneous reactant mixture and providing a good starting point for subsequent reactions. It can also increase the reaction rate, making subsequent reactions easier to proceed, thereby improving product quality.

[0016] In some embodiments of this application, the ball milling process is intermittent ball milling. The intermittent ball milling procedure includes: working for 3-5 minutes, then pausing for 1.5-2.5 minutes. Using intermittent ball milling, i.e., working for a period of time followed by a pause, with the procedure including working for 3-5 minutes and then pausing for 1.5-2.5 minutes, can effectively control heat, reduce wear, improve mixing efficiency, and optimize reaction conditions, thereby laying the foundation for the final preparation of materials with good properties.

[0017] In some embodiments of this application, compression molding includes pressing at a pressure of 20-100 MPa for 1-5 minutes. By pressing at a pressure of 20-100 MPa for 1-5 minutes, the efficiency of the preparation process can be maintained while ensuring the consistency and controllability of the resulting product, thereby improving product quality. This helps to make the preparation process more economical, environmentally friendly, and sustainable.

[0018] Thirdly, embodiments of this application provide a solid electrolyte sheet, including any of the aforementioned solid electrolyte materials.

[0019] Fourthly, embodiments of this application provide an all-solid-state battery, including the aforementioned solid electrolyte sheet. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is an assembly diagram of the high-voltage synthesis block in this application;

[0022] Figure 2 The XRD patterns are those of the solid electrolyte materials prepared in Examples 1-3 of this application;

[0023] Figure 3 The XRD patterns are those of the solid electrolyte materials prepared in Examples 4-7 of this application;

[0024] Figure 4 The XRD patterns of the solid electrolyte materials prepared in Examples 8-9 of this application are shown.

[0025] Figure 5 Linear voltammetric scans of the solid electrolyte materials provided in Examples 2, 5, 9 and the comparative examples of this application;

[0026] Figure 6 The results of the lithium cycle stability test in Test Example 2 of this application;

[0027] Figure 7 for Figure 6 A magnified view of a portion of the image.

[0028] Icons: 101-Steel cap plug; 102-Molybdenum sheet; 103-Graphite tube; 104-Graphite sheet; 105-Graphite column; 201-Pyrophyllite; 202-Pyrophyllite block; 301-Hexagonal boron nitride tube; 302-Hexagonal boron nitride sheet; 400-Blank. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0030] This application provides a solid electrolyte material, including a cubic phase M y OHA my-1-nx B x Wherein, M is a metal cation with a chemical valence state of m, A includes one or more of F, Cl, Br, and I, and B is an N-containing anion with a chemical valence state of -n, where n = 1-3; M includes Li + Na + K + Mg 2+ Ca 2+ 、Sr 2+ Zn 2+ Y 3+ La 3+ Al 3+ Ga 3+ Ti 4+ and Zr 4+ One or more of the following. The performance improvement mechanism of the solid electrolyte material provided in this application mainly stems from the synergistic effect of multiple factors. First, nitrogen doping introduces lattice defects, increasing the available vacancies for ion transport, thereby effectively improving conductivity. Second, the material forms a cubic phase crystal with a stable structure, ensuring long-term structural stability during use and guaranteeing the reliability of ionic conductivity. Furthermore, by reducing the ion transfer activation energy, ions can migrate more easily in the lattice even at relatively low temperatures, further improving the ionic conductivity of the electrolyte.

[0031] In this embodiment of the application, B includes N. 3- NH2 - and NH 2- One or more of the following. N 3- NH2 - and NH 2-The presence of nitrogen-containing anions in the crystal structure introduces additional bonds, enhancing lattice stability. This helps electrolyte materials maintain their structural integrity under different conditions (e.g., high temperature, high pressure), improving their long-term stability. Furthermore, the introduction of these nitrogen-containing anions can influence the lattice structure, altering charge balance and ion transport pathways, thereby modulating ion transport properties. For example, it can lower the activation energy for ion transfer in the lattice; by reducing this energy barrier, ions migrate more easily within the lattice, improving the ionic conductivity of the electrolyte material. In addition, these nitrogen-containing anions may also further enhance ionic conductivity by providing additional conductive pathways and optimizing ion migration within the lattice.

[0032] In some embodiments of this application, M is Li, and the solid electrolyte material includes an anti-perovskite cubic phase Li₂OHA doped with Li₂O. 1-nx B x The cubic phase Li2OHA 1-nx B x Including but not limited to anti-perovskite cubic phase Li2OHCl doped with Li2O 1-3x N x cubic phase Li2OHCl 1-x (NH2) x and cubic phase Li2OHCl 1-2x (NH) x At least one of the following. For example, anti-perovskite cubic phase Li₂OHCl doped with Li₂O. 0.85 N 0.05 cubic phase Li2OHCl 0.7 N 0.1 cubic phase Li2OHCl 0.4 N 0.2 cubic phase Li2OHCl 0.7 (NH2) 0.3 cubic phase Li2OHCl 0.6 (NH2) 0.4 cubic phase Li2OHCl 0.8 (NH) 0.1 and cubic phase Li2OHCl 0.6 (NH) 0.2 Because this solid electrolyte material is doped with Li₂O, the Li₂O will further react with the anti-perovskite cubic phase Li₂OHA. 1-nx B x This forms a composite electrolyte, thereby increasing the ionic conductivity and electrochemical stability of the electrolyte material.

[0033] The preparation method of this solid electrolyte material will be further explained below.

[0034] Its preparation method is as follows:

[0035] (1) Calculate the mass of raw materials to be weighed according to the stoichiometric ratio, weigh and mix lithium salts with different molar ratios, such as lithium compounds containing N elements such as LiOH, LiCl, Li3N, LiNH2 and Li2NH.

[0036] In this application, the solid electrolyte material includes Li2OHCl, an anti-perovskite cubic phase doped with Li2O. 1-3x N x The raw materials include LiOH, LiCl and Li3N, with a molar ratio of 1:(1-3x):x, and x = 0.05-0.2.

[0037] Alternatively, solid electrolyte materials may include anti-perovskite cubic phase Li2OHCl doped with Li2O. 1-x (NH2) x The raw materials include LiOH, LiCl and LiNH2, with a molar ratio of 1:(1-x):x, and x = 0.3-0.4.

[0038] Alternatively, solid electrolyte materials may include anti-perovskite cubic phase Li2OHCl doped with Li2O. 1-2x (NH) x The raw materials include LiOH, LiCl and Li2NH, and the molar ratio of LiOH, LiCl and Li2NH is 1:(1-2x):x, and x = 0.1-0.2.

[0039] (2) Pour the weighed raw materials into a zirconia / agate ball mill jar (containing zirconia / agate grinding beads and gaskets), tighten the jar to seal it, and then transfer the jar to a high-energy ball mill for thorough grinding. The milling speed is 350-500 r / min (working for 3-5 min, pausing for 1.5-2.5 min), and the milling time is 6-12 h to obtain powder. The total mass ratio of raw materials to grinding beads is 1:(10-30).

[0040] The ball milling process described in this application is intermittent ball milling, and the pauses in intermittent ball milling help dissipate heat. Since a large amount of frictional heat may be generated during ball milling, periodic pauses can mitigate the temperature rise caused by friction, helping to maintain the temperature of the ball milling system within an appropriate range. Continuous ball milling can lead to excessive wear on the grinding balls and containers, thereby reducing equipment lifespan. By setting pause times, the degree of mechanical wear can be reduced, extending the service life of the ball milling device. Simultaneously, the periodic pauses in intermittent ball milling help improve the uniform mixing of raw materials. During operation, the grinding balls grind and mix the raw materials, while during pauses, the raw materials can redistribute, enhancing the mixing effect.

[0041] In this application, by controlling the ball mill rotation speed to 350-500 r / min and the milling time to 6-12 h, sufficient mechanical energy input can be provided to promote thorough mixing and grinding between the raw materials and the milling beads. This helps eliminate particle inhomogeneity in the raw materials, forming a homogeneous reactant mixture and providing a good starting point for subsequent reactions. It can also increase the reaction rate, making subsequent reactions easier to proceed, thereby improving product quality.

[0042] In this application, by limiting the ratio of the total mass of raw materials to the mass of the milling beads to a range of 1:(10-30), the raw materials can be mixed evenly and ground thoroughly, achieving high efficiency and controllability of the ball milling process, thereby providing good reaction conditions for subsequent steps and improving the quality and performance of the final product.

[0043] (3) Weigh an appropriate amount of the ground powder sample from step (2) in a glove box, and press it for 1-5 minutes at 20-100 MPa using a manual tablet press to obtain a preform 400. The preform 400 can be a cylindrical block with a diameter of 6-10 mm. By controlling the pressure at 20-100 MPa and the pressing time at 1-5 minutes, the resulting product can be made more uniform and its density increased. Under 20-100 MPa pressure, the raw material is more easily compacted, forming a denser structure, which helps improve the mechanical strength and electrical conductivity of the material. Furthermore, it can reduce the energy consumption of the entire preparation process, thereby reducing the preparation cost.

[0044] (4) Assemble the pre-pressed blank 400 from step (3) using a pyrophyllite mold (this process is completed in a glove box) into a high-pressure synthesis block. Then, place the high-pressure synthesis block into a primary press for high-temperature and high-pressure synthesis experiments (1-5 GPa, 300-800℃) and hold it for 30-60 minutes. After depressurization, take out the sample that has completed the reaction during assembly, place it in a mortar and grind it evenly by hand to obtain the solid electrolyte material M. y OHA my-1-nx B x .

[0045] In this preparation method, ball milling can improve the uniformity and mixing degree of raw materials, promoting better mixing of various raw materials to form a homogeneous reactant mixture; it also helps to improve preparation efficiency and shorten reaction time; furthermore, by adjusting the synthesis conditions, such as high pressure (1-5 GPa), temperature (300-800℃) and synthesis time (30-60 min), it is beneficial to form a cubic phase crystal with a stable structure, which helps to improve the mechanical strength and long-term stability of the electrolyte material, while optimizing the ion transport path, thereby improving the conductivity.

[0046] The synthesis press used in this application is a two-sided top press or a six-sided top large-cavity press. The synthesis pressure in this application includes, but is not limited to, 1 GPa, 2 GPa, 3 GPa, 4 GPa, and 5 GPa; the synthesis temperature includes, but is not limited to, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, and 800℃; the synthesis time includes, but is not limited to, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min; the synthesis time is not limited to, but is not limited to, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min.

[0047] In the above preparation scheme, the high-pressure synthesis block is assembled as follows: the pre-pressed blank 400 is placed into a hexagonal boron nitride tube, and the upper and lower ends of the hexagonal boron nitride tube are sealed with hexagonal boron nitride discs; then the sealed hexagonal boron nitride tube is placed into a graphite tube 103, and the upper and lower ends of the graphite tube 103 are sealed with graphite discs 104; then, pyrophyllite 201 with built-in graphite pillars 105, molybdenum sheet 102, and steel cap plug 101 are sequentially added to the top of the graphite tube 103. All components are interference-fitted, and the assembly is finally placed into the pyrophyllite block 202 to form the high-pressure synthesis block. Please refer to the assembly diagram of the high-pressure synthesis block. Figure 1 ,like Figure 1 As shown, the high-pressure synthesis block, from top to bottom, consists of a steel cap plug 101, a molybdenum sheet 102, and a carbon tube that conduct electricity and heat the sample by applying current. Pyrophyllite 201 and pyrophyllite block 202 transmit pressure, transferring pressure to the internal sample through pyrophyllite 201. Hexagonal boron nitride sheet 302 and hexagonal boron nitride tube 301 provide heat preservation and pressure maintenance.

[0048] The method for preparing the solid electrolyte material provided in this application utilizes equipment to provide high-temperature and high-pressure experimental conditions, using several nitrogen-containing lithium compounds selected from LiOH, LiCl, Li3N, LiNH2, and Li2NH as raw materials to carry out a synthesis reaction, thereby obtaining the solid electrolyte material M. y OHA my-1-nx B x Where M is Li, the solid electrolyte material comprises an anti-perovskite cubic phase Li₂OHCl doped with Li₂O. 1-3x N x cubic phase Li2OHCl 1-x (NH2) x and cubic phase Li2OHCl 1-2x (NH) x At least one of the following. Synthetic cubic phase Li₂OHCl 1-3x N x cubic phase Li2OHCl1-x (NH2) x and cubic phase Li2OHCl 1-2x (NH) x The reaction equations involved are as follows:

[0049] (1)LiOH+(1-3x)LiCl+xLi3N→Li2OHCl 1-3x N x

[0050] (2)LiOH+(1-x)LiCl+xLiNH2→Li2OHCl 1-x (NH2) x

[0051] (3)LiOH+(1-2x)LiCl+xLi2NH→Li2OHCl 1-2x (NH) x

[0052] The inventors discovered through experiments that when the solid electrolyte material is cubic Li₂OHCl... 1-3x N x When the raw materials LiOH and Li3N used to synthesize this electrolyte material are at a reaction temperature below 350℃, they will undergo a reversible reaction to generate Li2O; then, they will combine with LiCl to generate the anti-perovskite electrolyte material Li2OHCl. 1-3x N x This reacts with the generated Li₂O to form a composite electrolyte. The doping of Li₂O further enhances the ionic conductivity of this electrolyte material. The relevant chemical reaction equations are as follows:

[0053]

[0054]

[0055] LiOH+(1-3x)LiCl+xLi3N→Li2OHCl 1-3x N x Formula III

[0056] The features and performance of this application will be further described in detail below with reference to the embodiments.

[0057] Example 1

[0058] This embodiment provides a solid electrolyte material, the preparation method of which is as follows:

[0059] (1) Weigh LiOH, LiCl, and Li3N in a molar ratio of 1:0.85:0.05, and pour the weighed raw materials into a zirconia / agate ball mill jar (containing zirconia / agate grinding beads and gaskets). Tighten the jar to ensure it is sealed, and then transfer the jar to a high-energy ball mill for thorough grinding. The milling speed is 450 r / min (4 min working, 2 min pause), and the milling time is 6 h to obtain powder. The total mass ratio of the raw materials to the grinding beads is 1:20.

[0060] (2) Weigh an appropriate amount of the ground powder sample from step (1) in the glove box, and press it for 4 minutes at 100 MPa using a manual tablet press to obtain a blank 400.

[0061] (3) Assemble the pre-pressed blank 400 from step (2) using a pyrophyllite mold (this process is completed in a glove box) into a high-pressure composite block (see assembly diagram). Figure 1 The high-pressure synthesis block was then placed in a primary press for high-temperature and high-pressure synthesis experiments (3 GPa, 400℃) for 50 minutes. After depressurization, the sample that had completed the reaction during assembly was removed, placed in a mortar, and manually ground until homogeneous to obtain Li2O-doped anti-perovskite cubic phase Li2OHCl. 0.85 N 0.05 .

[0062] Example 2

[0063] This embodiment is basically the same as Embodiment 1, except that in step (1), LiOH, LiCl and Li3N are weighed in a molar ratio of 1:0.7:0.1 and then reacted to obtain an anti-perovskite cubic phase Li2OHCl doped with Li2O. 0.7 N 0.1 .

[0064] Example 3

[0065] This embodiment is basically the same as Embodiment 1, except that in step (1), LiOH, LiCl and Li3N are weighed in a molar ratio of 1:0.4:0.2 and then reacted to obtain an anti-perovskite cubic phase Li2OHCl doped with Li2O. 0.4 N 0.2 .

[0066] Example 4

[0067] This embodiment provides a solid electrolyte material, the preparation method of which is as follows:

[0068] (1) Weigh LiOH, LiCl, and LiNH2 in a molar ratio of 1:0.9:0.1, and pour the weighed raw materials into a zirconia / agate ball mill jar (containing zirconia / agate grinding beads and gaskets). Tighten the jar to ensure it is sealed, and then transfer the jar to a high-energy ball mill for thorough grinding. The milling speed is 450 r / min (4 min working, 2 min pause), and the milling time is 6 h to obtain powder. The total mass ratio of the raw materials to the grinding beads is 1:20.

[0069] (2) Weigh an appropriate amount of the ground powder sample from step (1) in the glove box, and press it for 4 minutes at 100 MPa using a manual tablet press to obtain a blank 400.

[0070] (3) Assemble the pre-pressed blank 400 from step (2) using a pyrophyllite mold (this process is completed in a glove box) into a high-pressure composite block (see assembly diagram). Figure 1 The high-pressure synthesis block was then placed in a primary press for high-temperature and high-pressure synthesis experiments (3 GPa, 400℃) for 50 min. After depressurization, the sample that had completed the reaction during assembly was removed, placed in a mortar, and manually ground until homogeneous to obtain the anti-perovskite cubic phase Li₂OHCl. 0.9 (NH2) 0.1 .

[0071] Example 5

[0072] This embodiment is basically the same as embodiment 4, except that in step (1), LiOH, LiCl and LiNH2 are weighed in a molar ratio of 1:0.8:0.2 and then reacted to obtain an anti-perovskite cubic phase Li2OHCl doped with Li2O. 0.8 (NH2) 0.2 .

[0073] Example 6

[0074] This embodiment is basically the same as embodiment 4, except that in step (1), LiOH, LiCl and LiNH2 are weighed in a molar ratio of 1:0.7:0.3 and then reacted to obtain an anti-perovskite cubic phase Li2OHCl doped with Li2O. 0.7 (NH2) 0.3 .

[0075] Example 7

[0076] This embodiment is basically the same as embodiment 4, except that in step (1), LiOH, LiCl and LiNH2 are weighed in a molar ratio of 1:0.6:0.4 and then reacted to obtain an anti-perovskite cubic phase Li2OHCl doped with Li2O. 0.6 (NH2) 0.4 .

[0077] Example 8

[0078] This embodiment provides a solid electrolyte material, the preparation method of which is as follows:

[0079] (1) Weigh LiOH, LiCl, and Li₂NH in a molar ratio of 1:0.8:0.1, and pour the weighed raw materials into a zirconia / agate ball mill jar (containing zirconia / agate grinding beads and gaskets). Tighten the jar to seal it, and then transfer it to a high-energy ball mill for thorough grinding. The milling speed is 450 r / min (4 min working, 2 min pause), and the milling time is 6 h to obtain powder. The total mass ratio of the raw materials to the grinding beads is 1:20.

[0080] (2) Weigh an appropriate amount of the ground powder sample from step (1) in the glove box, and press it for 4 minutes at 100 MPa using a manual tablet press to obtain a blank 400.

[0081] (3) Assemble the pre-pressed blank 400 from step (2) using a pyrophyllite mold (this process is completed in a glove box) into a high-pressure composite block (see assembly diagram). Figure 1 The high-pressure synthesis block was then placed in a primary press for high-temperature and high-pressure synthesis experiments (3 GPa, 400℃) for 50 minutes. After depressurization, the sample that had completed the reaction during assembly was removed, placed in a mortar, and manually ground until homogeneous to obtain Li2O-doped anti-perovskite cubic phase Li2OHCl. 0.8 (NH) 0.1 .

[0082] Example 9

[0083] This embodiment is basically the same as Embodiment 8, except that in step (1), LiOH, LiCl and Li2NH are weighed in a molar ratio of 1:0.6:0.2 and then reacted to obtain an anti-perovskite cubic phase Li2OHCl doped with Li2O. 0.6 (NH) 0.2 .

[0084] Comparative Example

[0085] This comparative example is the same as Example 1, except that in step (1), LiOH and LiCl are weighed in a molar ratio of 1:1 and then reacted to obtain the target product Li2OHCl.

[0086] Experimental Example 1

[0087] In this experimental example, the solid electrolyte materials prepared in Examples 1-9 and the comparative examples were subjected to X-ray diffraction to analyze the phase structure of the electrolyte materials; among them, the XRD patterns of the solid electrolyte materials prepared in Examples 1-3 are as follows: Figure 2 As shown; the XRD patterns of the solid electrolyte materials prepared in Examples 4-7 are as follows. Figure 3 As shown; the XRD patterns of the solid electrolyte materials prepared in Examples 8-9 are as follows. Figure 4 As shown.

[0088] from Figures 2-4 It can be seen that the raw materials react completely, and the N-containing ions are completely doped into the halide anti-perovskite system. Furthermore, the solid electrolyte material has good crystallinity and no characteristic peaks of Li3N, LiNH2, or Li2NH.

[0089] In addition, from Figure 2 and Figure 4 It can also be seen that the solid electrolyte materials prepared in Examples 1-3 have characteristic Li2O peaks at 33.58°, 38.97°, 56.59°, and 67.16°, indicating that the solid electrolyte materials are doped with Li2O. This suggests that during the synthesis of the above electrolyte materials, LiOH and Li3N first undergo a reversible reaction of Formula I-Formula II to generate Li2O; then, it combines with LiCl to generate the anti-perovskite electrolyte material Li2OHCl. 1-3x N x (Formula III) and forms a composite electrolyte with the generated Li₂O; the solid electrolyte materials prepared in Examples 7-9 also show characteristic Li₂O peaks at 33.58°, 38.97°, 56.59°, and 67.16°. Figure 3 It can be seen that when the LiNH2 doping ratio is 30% and 40%, that is, the solid electrolyte material is the anti-perovskite cubic phase Li2OHCl 0.7 (NH2) 0.3 and cubic phase Li2OHCl 0.6 (NH2) 0.4 At the same time, characteristic peaks of Li2O also appear.

[0090] Experimental Example 2

[0091] I. Determination of Ionic Conductivity: 100-150 mg of solid electrolyte material samples prepared in Examples 1-9 and the comparative examples were placed in a mold battery with a diameter of 10 mm. A force of 3 T was applied on a hydraulic press, and the temperature-dependent ionic conductivity was measured using an electrochemical workstation (temperature range of 25-120℃, with a temperature gradient of 20℃). The ionic conductivity at the corresponding temperature was calculated by substituting the AC impedance data into the formula: σ=d / (R×A) (σ - ionic conductivity, d - thickness of the solid electrolyte film, R - impedance, A - cross-sectional area of ​​the solid electrolyte film).

[0092] The ionic conductivity data of the above solid electrolyte materials at 25℃ are shown in Table 1.

[0093] Table 1

[0094] Example 1 <![CDATA[3.40×10 -6 ]]> Example 2 <![CDATA[1.35×10 -5 ]]> Example 3 <![CDATA[2.97×10 -6 ]]> Example 4 <![CDATA[3.42×10 -6 ]]> Example 5 <![CDATA[8.68×10 -6 ]]> Example 6 <![CDATA[5.31×10 -6 ]]> Example 7 <![CDATA[3.90×10 -6 ]]> Example 8 <![CDATA[5.73×10 -6 ]]> Example 9 <![CDATA[8.29×10 -6 ]]> Comparative Example <![CDATA[1.11×10 -6 ]]>

[0095] As can be seen from Table 1, Li₂OHCl 0.7 N 0.1 The ionic conductivity at 25℃ is 1.35 × 10⁻⁶. -5 S·cm -1 Li2OHCl 0.9 (NH2) 0.1 The ionic conductivity at 25℃ can reach as high as 8.68 × 10⁻⁶. -6 S·cm -1 Li2OHCl 0.6 (NH) 0.2 The ionic conductivity at 25℃ can reach as high as 8.29 × 10⁻⁶. -6 S·cm -1 .

[0096] from Figure 3 It can be seen that the solid electrolyte prepared in Example 4 does not have the characteristic peak of Li2O, that is, the solid electrolyte does not have Li2O doping, while the solid electrolytes in Examples 6 and 7 do have the characteristic peak of Li2O. Comparing Examples 4, 6 and 7, it can be seen that since Li2O is generated during the reaction process, Li2O will be doped into the anti-perovskite solid electrolyte material, thereby further improving the ionic conductivity.

[0097] 2. Linear voltammetric scanning curves were measured using an electrochemical workstation to estimate the electrochemical window.

[0098] 130 mg of the solid electrolyte material samples provided in Examples 2, 5, 9, and the comparative example were placed into a mold battery with a diameter of 10 mm, and a force of 3 T was applied on a hydraulic press. A mixture of electrolyte material powder and carbon black in a 5:1 mass ratio was spread on the sample surface as the positive electrode, and a force of 3 T was applied again. A lithium foil with a thickness of less than 100 μm and a diameter of 7 mm was attached as the negative electrode to the center of the other end of the electrolyte material. The mold battery was kept in a 60 °C oven for 1 hour, and then the electrochemical window was estimated by linear voltammetry curve testing using a Solartron electrochemical workstation.

[0099] Linear voltammetric scans of the solid electrolyte materials provided in Examples 2, 5, 9 and Comparative Examples are shown below. Figure 5 As shown.

[0100] from Figure 5 As can be seen from this, Li2OHCl 0.7 N 0.1 Li2OHCl 0.8 (NH2) 0.2 and Li2OHCl 0.6 (NH) 0.2 The oxidation voltages were 4.92V, 3.94V, and 4.08V, respectively. Compared with Li₂OHCl (3.84V), the electrochemical window of the battery fabricated with the solid electrolyte material provided in this application is significantly improved. Among them, Li₂OHCl... 0.8 (NH2) 0.2 It is not doped with Li₂O, Li₂OHCl 0.7 N 0.1 and Li2OHCl 0.6 (NH) 0.2 It is doped with Li2O, which shows that Li2O doping can also improve the electrochemical window of the battery.

[0101] III. Lithium Cycle Stability Test

[0102] 120 mg of the solid electrolyte material sample provided in Example 2 was placed into a mold battery with a diameter of 10 mm, and a force of 3 T was applied on a hydraulic press. Lithium foil with a thickness of less than 100 μm and a diameter of 6 mm was attached to the center of both ends of the electrolyte for both the positive and negative electrodes. The sample was then kept in a 120°C oven for 6 hours, and the lithium cycle stability was tested using a Landian battery tester. The results of the lithium cycle stability test are as follows: Figure 6 and Figure 7 As shown.

[0103] from Figure 6 and Figure 7It can be seen that the voltage plateau remains very stable during the 170-hour charge-discharge cycle. However, starting from around 175 hours, the polarization voltage begins to increase rapidly. This may be due to the growth of lithium dendrites, which causes a sudden drop in the battery's polarization voltage, leading to short-circuit failure.

[0104] The embodiments described above are some, but not all, of the embodiments of this application. The detailed description of the embodiments of this application is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.

Claims

1. A solid electrolyte material, characterized in that, Including the anti-perovskite cubic phase Li2OHA 1-nx B x Wherein, A includes one or more of F, Cl, Br and I, and B is an N-containing anion with a chemical valence state of -n, where n = 1-3, and B includes N 3- NH2 - and NH 2- One or more of the following; the anti-perovskite cubic phase Li2OHA 1-nx B x It is doped with Li2O, but not with Li3N, LiNH2, or Li2NH.

2. The solid electrolyte material according to claim 1, characterized in that, The solid electrolyte material includes Li2OHA, an anti-perovskite cubic phase doped with Li2O. 1-nx B x The cubic phase Li2OHA 1-nx B x Including anti-perovskite cubic phase Li2OHCl doped with Li2O 1-3x N x cubic phase Li2OHCl 1-x (NH2) x and cubic phase Li2OHCl 1-2x (NH) x At least one of them.

3. The solid electrolyte material according to claim 2, characterized in that, The cubic phase Li2OHA 1-nx B x Including anti-perovskite cubic phase Li2OHCl doped with Li2O 0.85 N 0.05 cubic phase Li2OHCl 0.7 N 0.1 cubic phase Li2OHCl 0.4 N 0.2 cubic phase Li2OHCl 0.7 (NH2) 0.3 cubic phase Li2OHCl 0.6 (NH2) 0.4 cubic phase Li2OHCl 0.8 (NH) 0.1 and cubic phase Li2OHCl 0.6 (NH) 0.2 At least one of them.

4. A method for preparing a solid electrolyte material as described in any one of claims 1-3, characterized in that, include: The raw materials are mixed according to the metered ratio and then ball-milled to obtain powder; the powder is pressed into shape to obtain a blank; the blank is then subjected to synthesis at 1-5 GPa and 300-800℃ for 30-60 min to obtain the solid electrolyte material.

5. The preparation method according to claim 4, characterized in that, The solid electrolyte material includes an anti-perovskite cubic phase Li2OHCl doped with Li2O. 1-3x N x The raw materials include LiOH, LiCl and Li3N, and the molar ratio of LiOH, LiCl and Li3N is 1:(1-3x):x, where x=0.05-0.2; Alternatively, the solid electrolyte material may comprise an anti-perovskite cubic phase Li2OHCl doped with Li2O. 1-x (NH2) x The raw materials include LiOH, LiCl and LiNH2, and the molar ratio of LiOH, LiCl and LiNH2 is 1:(1-x):x, where x=0.3-0.4; Alternatively, the solid electrolyte material may comprise an anti-perovskite cubic phase Li2OHCl doped with Li2O. 1-2x (NH) x The raw materials include LiOH, LiCl and Li2NH, and the molar ratio of LiOH, LiCl and Li2NH is 1:(1-2x):x, where x=0.1-0.

2.

6. The preparation method according to claim 4, characterized in that, The ball milling process includes: the total mass of the raw material to the mass of the milling beads is 1:(10-30).

7. The preparation method according to any one of claims 4-6, characterized in that, The ball mill rotates at a speed of 350-500 r / min, and the milling time is 6-12 h.

8. The preparation method according to claim 7, characterized in that, The ball milling process is intermittent ball milling, and the intermittent ball milling procedure includes: working for 3-5 minutes and pausing for 1.5-2.5 minutes.

9. The preparation method according to any one of claims 4-6, characterized in that, The compression molding process includes pressing under a pressure of 20-100 MPa for 1-5 minutes.

10. A solid electrolyte sheet, characterized in that, Includes the solid electrolyte material according to any one of claims 1-3.

11. An all-solid-state battery, characterized in that, Includes the solid electrolyte sheet as described in claim 10.

Citation Information

Patent Citations

  • Solid electrolyte, preparation method thereof and all-solid-state battery

    CN112768754A

  • Solid electrolyte and / or electroactive material

    US20170025705A1